2004
DOI: 10.1080/14767050410001728935
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal serum α-fetoprotein with persistent placenta previa

Abstract: There is an association between increasing MSAFP values and greater likelihood of persistent placenta previa. An MSAFP value <1 MoM is associated with a reduction in the risk of persistence of previa to delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several groups of researchers have investigated the role of the placenta in the transport and possible synthesis of AFP in situ [28,[69][70][71] following a report that AFP was synthesized by the first trimester human placenta [72]. These investigations sought to probe for the placental expression of AFP in trophoblast cells of normal pregnancies at full term.…”
Section: Afp and Afp-receptor Expression In The Normal Human Placentamentioning
confidence: 98%
“…Several groups of researchers have investigated the role of the placenta in the transport and possible synthesis of AFP in situ [28,[69][70][71] following a report that AFP was synthesized by the first trimester human placenta [72]. These investigations sought to probe for the placental expression of AFP in trophoblast cells of normal pregnancies at full term.…”
Section: Afp and Afp-receptor Expression In The Normal Human Placentamentioning
confidence: 98%
“…MSα‐FP of 1.5 MoM or above had a sensitivity of 29% and a false positive rate of 10% to predict abruption. Koster et al showed an association between elevated increasing MSα‐FP values and greater likelihood of persistent placenta praevia at term. Both Kupferminc et al and Zelop et al retrospectively analysed serum MSα‐FP levels in women that underwent caesarean hysterectomies for placenta accreta, percreta or increta and matched them to controls that underwent caesarean hysterectomies for other reasons.…”
Section: Second Trimester Markersmentioning
confidence: 99%
“…The authors of several studies have investigated the role of the placenta in the transport and possible synthesis of ATP in situ (77)(78)(79)(80), since an earlier report showed that AFP was synthesized by the firsttrimester human placenta (81). The objective of these investigations was to probe for the placental expression of AFP and its receptor in trophoblast cells of normal pregnancies at full term.…”
Section: Structural and Functional Aspects Of Afpmentioning
confidence: 98%